Spying on Ireland British intelligence and Irish neutrality during the Second World War - O'Halpin, Eunan (Oxford University Press, 2008)
Irish neutrality during the Second World War presented Britain with significant challenges to its security. Exploring how British agencies identified and addressed these problems, Eunan O'Halpin casts light on the significance of both espionage and cooperation between agencies for developing wider relations between the two countries.